THE INFLUENCE OF MATRIX RHEOLOGY AND VORTICITY ON FABRIC DEVELOPMENT OF POPULATIONS OF RIGID OBJECTS DURING PLANE STRAIN DEFORMATION - Piazolo S.; Bons P.D.; Passchier C.W. (My University, 2002)
The influence of vorticity and rheology of matrix material on the development of shape-preferred orientation (SPO) of populations of rigid objects was experimentally studied. Experiments in plane strain monoclinic flow were performed to model the fabric development of two populations of rectangular rigid objects with object aspect ratios (Rob) 2 and 3. The density of the rigid object populations was 14% of the total area. Objects were dispersed in a Newtonian and a non-Newtonian, power law matrix material with a power law exponent n of 1.2. The kinematic vorticity number (Wn) of the plane strain monoclinic flow was 1, 0.8 and 0.6 with finite simple shear strain of 4.6, 3.0 and 0.9, respectively. In experiments with Rob=3, the SPO is strongly influenced by Wn and the material properties of the matrix. Deformation of a power law matrix material and low Wn resulted in a stronger SPO than deformation of a linear viscous matrix and high Wn. Strain localization coupled with particle interaction plays a significant role in the development of a shape-preferred orientation. High strain simple shear zones separate trains of rigid objects that are surrounded by low strain zones with Wn lower than the bulk Wn. In fabrics involving populations of objects with Rob=2, rheology of the matrix materials does not systematically influence the intensity of the SPO.
Keywords: ANALOGUE MODELLING; SHAPE-PREFERRED ORIENTATION; GENERAL FLOW; STRAIN LOCALIZATION; POWER LAW FLOW